21th century physics learning in senior high school through interactive computer simulation to enhance students achievement - A Swandi; B D Amin; F Muin (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to harness interactive computer simulation on physics concept that have been developed to improve students achievement by determining the differences in physics learning outcomes of students who were taught using computer simulations with students who were taught using conventional media and also evaluating students activity and their perception. The research type is true experiment with Posttest-Only Control Design. The research instrument used is the test of physics learning result of 20 questions in the form of multiple choice test which has valid on